Eosinophilic Fasciitis in a Patient with Hepatitis C Virus Infection: Coincidence or Association? - Samuel Katsuyuki Shinjo; Fernando Henrique Carlos de Souza (Rheumatica Acta: Open Access - Peertechz Publications, 2017)
Eosinophilic fasciitis is a rare connective tissue disease characterized by symmetrical and painful swelling with a progressive induration and thickening of the skin and soft tissues. Its etiology is unknown, but possible causes or associated conditions include drugs, physical exercises, autoimmune diseases, neoplasia and infections.         Herein, we report, at the fi rst time in the literature, the eosinophilic fasciitis in a patient with hepatitis C virus infection.